YIELD PERFORMANCE AND PRODUCTION EFFICIENCY OF MIXED AND SOLE CROPPING UNDER DIFFERENT FALLOW CYCLE OF SHIFTING CULTIVATION IN NORTHEAST INDIA - H. C. KALITA; VISHRAM RAM (The Bioscan, 2015)
A field experiment was conducted during 2013-14 on yield performance and production efficiency of crops. The crops were grown as mixed and sole cropping system in 5, 10 and 20 years cycle of shifting and or jhum field. The rice equivalent yield (REY) was the highest in ginger sole cropping. It was followed by colocasia, mixed crops, sesamum, okra, brinjal, chilli, maize and rice, respectively. The REY was increased along with increased with fallow length (5, 10 and 20 years). Mixed cropping system increased the production efficiency (PE) from 12.21 to 502.96 percent. The PE of ginger (sole) increased by 20.5, 24.71 and 25.10 percent in 5, 10 and 20 years cycles respectively. Similarly, the PE of colocasia (sole) was increased by 10.13 and 3.23 percent in 5 and 10 years fallow cycle. The total uptake of N, P and K by crops was more in 20 years fallow cycle, followed by 10 and 5 years cycle. The mixed crop removes highest N and P in all cycles than the sole. But K uptake was higher in 20 years cycle by ginger.